Design Construction and Performance of Nanostructured P-Cu2s/N-Cds Junction Diode - Singh, D (Elsevier B.V., 2023)
Here we report the deposition of Cu2S/CdS thin-film on FTO substrate through spray-pyrolysis technique. The sizes of the thin-film are estimated through field-emission scanning electron microscopy(FESEM) images,exhibited that the films are mono-dispersed, and nearly spherical with the average size lies in the range of 50 nm to 100 nm, which increases with increasing the temperature. The effect of temperature on the performance of Sn/Cu2S/CdS/FTO/glass hetrojunction diodes are analyzed through I–V measurement. The diode parameters such as potential height, leakage current, ideality factor and series-shunt resistance are calculated through conventional thermionic-emission, Cheung and Norde models. It is observed that the ideality factor decreases from 1.31 to 1.12 and potential height increases from 0.79 to 0.86, as temperature increases from thermionic emission model. The diode parameter values estimated from these three different methods are in good agreement. © 2022 Elsevier B.V.